2012
DOI: 10.1007/s00284-012-0283-4
|View full text |Cite
|
Sign up to set email alerts
|

AppA C-terminal Plays an Important Role in its Thermostability in Escherichia coli

Abstract: Due to our previous research, mainly the thermostable mutants Q307D, Y311K, and I427L, we conjectured that Escherichia coli AppA phytase's C-terminal plays an important role in its thermostability, and AppA begins to collapse from the C-terminal when at a higher temperature. So here we constructed C-lose mutant to prove it. The residual activities of the wild-type AppA phytase and C-lose were 31.42 and 70.49 %, respectively, after being heated at 80 °C for 10 min. The C-terminal deletion mutant C-lose showed 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The helix was found to be very well conserved in the C-terminus until the simulated temperature rose to 500 K. In general, for most of the proteins, the N-terminus shows more flexibility than the C-terminus. Hence, it can be inferred from our results that either stabilizing or deleting the C-terminus could result in a thermostable variant [15]. The results obtained in this study are qualitative rather than quantitative.…”
Section: Conformational Changes During High-temperature Simulationmentioning
confidence: 40%
See 2 more Smart Citations
“…The helix was found to be very well conserved in the C-terminus until the simulated temperature rose to 500 K. In general, for most of the proteins, the N-terminus shows more flexibility than the C-terminus. Hence, it can be inferred from our results that either stabilizing or deleting the C-terminus could result in a thermostable variant [15]. The results obtained in this study are qualitative rather than quantitative.…”
Section: Conformational Changes During High-temperature Simulationmentioning
confidence: 40%
“…3c) which contribute greatly to the formation and stability of secondary structures. As the temperature is increased from 310 K to 400 K, the total number of main chain to main chain hydrogen bonds gradually decreases, implying that hydrogen bonding is an important factor in the thermostability of PhyA [12][13][14][15][16][17][18][19]. Also, the solvent-accessible surface area increases significantly at 500 K due to the unfolding of PhyA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the previous section, the C-terminal residues which form a flexible region were deleted to increase residual activity at 80°C [48]. In another report, the authors identified uncharged residues in the highly flexible areas on the protein surface with molecular dynamic simulation and 3D structures.…”
Section: Structure-based Designmentioning
confidence: 99%
“…ble 3 10 helix, which is considered prone to collapse at high temperatures. Indeed, deleting the C-terminal region resulted in 39 % higher residual activity at 80°C [48].…”
Section: Directed Evolutionmentioning
confidence: 99%